Estimación de biomasa y carbono almacenado en un fragmento de bosque húmedo tropical, CIEFOR, Puerto Almendra, Rio Nanay, Iquitos – 2023 - Panaifo Iruyari, Rosa Antonia (2025)
The study was carried out in a forest fragment with low terrace characteristics, a flood-prone area, of CIEFOR-Puerto Almendra. The overall objective was to estimatethe aboveground biomass and stored carbon in a tropical rainforest fragment, using two allometries or mathematical models, by diameter class and by tree species and in turn determine which allometric equation is appropriate from Álvarez (2012) cited by Casas (2013, p. 12); by Chave et al., (2014, p. 6). In this sense it is shown that biomass and stored carbon increase with the diameter increase of the trees, in the diameter class of 50 cm the highest values of biomass and stored carbon were reported for the Álvarez equationset al., (33656. 15 kg/ha, 16.83 t/ha) and Chavetet al., (45976.74 kg/ha, 22.99 t/ha). The speciesNealchornea yapurensis and Pourouma acuminataThey were identified as the species with the greatest biomass and stored carbon with the Alvarez equationset al., (27031.14 kg/ha, 23618.63 kg/ha; 13.52 t/ha, 11.81 t/ha) and Chavetet al., (40179.48 kg/ha, 27053.42 kg/ha; 20.09 t/ha, 13.53 t/ha). Chave's estimateset al. were consistently higher across all diameter classes, with a total biomass difference of 83,623.38 kg/ha (42.07% higher) and carbon difference of 41.81 t/ha. These differences were statistically significant (Wilcoxon test, p < 0.0001), although both equations showed a high correlation (r = 0.99, p < 0.0001).